EVALUASI KEBIJAKAN APLIKASI PLATFORM MERDEKA MENGAJAR DALAM PENGELOLAAN KINERJA GURU DI SMPN 3 KARANG BAHAGIA KABUPATEN BEKASI - Hidayat, Syarif; Mardisentosa, Bambang; Hardian, Dafyar Eliadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to evaluate the policy of using the Merdeka Mengajar (PMM) Platform for managing teacher performance at SMPN 3 Karang Bahagia, Bekasi Regency. PMM is a policy of the Ministry of Education, Culture, Research, and Technology designed to support the implementation of the Merdeka Curriculum and serve as an instrument for teacher development and performance assessment. The research method used was a qualitative descriptive approach, with data collection techniques through interviews, observation, and documentation. Data analysis was conducted using William N. Dunn's policy evaluation model, which encompasses six dimensions: effectiveness, efficiency, adequacy, fairness, responsiveness, and accuracy. The results indicate that the implementation of PMM at SMPN 3 Karang Bahagia has been quite effective in facilitating teachers' access to materials, reflection, and independent competency development. From an efficiency perspective, the use of PMM helps save time in performance reporting, although technical challenges related to the internet network remain. Regarding adequacy, PMM is considered to support most teachers' needs but has not fully resolved the administrative burden. In terms of fairness, platform access is relatively equitable for all teachers, but differences in digital literacy skills remain a challenge. The responsiveness aspect indicates that teachers feel the available features are helpful, although some features are not yet optimally utilized. Meanwhile, in terms of accuracy, this policy is deemed relevant to the need to improve educational quality but still requires improved infrastructure and ongoing mentoring. Overall, the policy for using the Merdeka Mengajar Platform at SMPN 3 Karang Bahagia can be considered positive and beneficial, although it still requires improvements, particularly in technical aspects and mentoring, to more optimally support teacher performance. Keywords: Policy evaluation, Merdeka Mengajar Platform, teacher performance.